AB0991 Current State of Musculoskeletal Ultrasound in JIA in France and Switzerland. (9th June 2015) - Rossi-Semerano, L.; Von Scheven-Gète, A.; Jousse-Joulin, S.; Devauchelle-Pensec, V.; Koné-Paut, I.; Hofer, M.
Abstract : Background: Musculoskeletal ultrasound (MSUS) is an established imaging tool for the diagnosis and follow-up of patients with rheumatic diseases. MSUS is widely used by adult rheumatologists in clinical practice. In the last decade, several papers have supported the value of MSUS for the diagnosis and management of juvenile idiopathic arthritis (JIA) 1, 2, nevertheless, the use of this tool in paediatric rheumatology practice is still limited. Objectives: To evaluate the current use of MSUS for JIA management in France and Switzerland. Methods: A questionnaire was developed by the US subgroup of the Juvenile Inflammatory Rheumatisms (JIR) project and it was send by e-mail to the members of the French and Swiss societies for paediatric rheumatology. Results: We collected questionnaires from 18 physicians (11 paediatric rheumatologists, 6 adult rheumatologists and 1 paediatric radiologist) out of 196 (9%). All relied on MSUS in their clinical practice but only 7 performed MSUS themselves. The number of MSUS examinations was relatively low, with less than 5 MSUS examinations per week for 71% and less than 10 per week for 29% of the participants. Concerning US techniques, grey-scale combined with power Doppler (PD) was the most used (60%). The main indication of MSUS at diagnosis was the detection of subclinical synovitis (83%), and the guidance for joint or tendon sheath injections (67% of participants). A minority of participants used MSUS to confirm the diagnosis of JIA (33%). Similar results were found regarding the use of MSUS during disease follow-up: detection of subclinical synovitis and guidance for injections for 72% of participants; moreover, MSUS was used to evaluate the response to treatment by 67%. Most participants used MSUS to evaluate painful or limited joints without clinical synovitis (78%) or for evaluating clinically inflamed joints (78%). Only 33% of participants used validated scoring systems, mainly the OMERACT semi-quantitative scoring systems for gray-scale and PD synovitis. Among the different JIA subtypes, MSUS was used in the following proportions: oligoarticular arthritis 48%, polyarticular arthritis 25%, spondyloarthritis 18, 2%, psoriatic arthritis 6, 3% and systemic arthritis 2, 5%. Conclusions: The experience with MSUS in the management of JIA is still limited in France and in Switzerland, like in the rest of Europe 3 . MSUS is commonly used to detect subclinical synovitis and to guide joint and tendon sheath injections 1, 2, thus, an improvement of the training of paediatric rheumatologists in MSUS is warranted. Moreover, standardization of healthy joints in growing children, consensus in the definition of synovitis and development of scoring systems are urgent needs in paediatric rheumatology. References: Karmazyn B et al. US findings of metacarpophalangeal joints in children with idiopathic juvenile arthritis. Pediatr Radiol 2007;37:475-82. Collado P et al. Is ultrasound a validated imaging tool for the diagnosis and management of synovitis in juvenile idiopathic arthritis? A systematic literature review.Arthritis Care Res 2012;64:1011-9. Magni-Manzoni S et al. Current state of musculoskeletal ultrasound in paediatric rheumatology: results of an international survey. Rheumatology 2014;53:491-496. Disclosure of Interest: None declared